Syntheses of polyesters and poly (ester-anhydrides) industrial applications - Erten, Ayşe Zeyneb. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Polyesters are one of the most important and widely used polymers in industry. Especially for powder coating application, the final properties of coating composition mainly depend on the polyester employed. These linear or branched polyesters are usually carboxylic acid terminated and thermally react with an epoxy hardener. The number of reactive end groups, the molecular weight, the viscosity, and the glass transition temperature (Tg) of polyesters affect the curing temperature and the levelling performance of the powder coating. For example, as the molecular weight of the polyester increases, Tg increases. This results in higher viscosity and thus poor levelling and surface quality. Therefore, in this study the aim was to synthesize poly(ester-anhydrides) that contains labile anhydride linkages. During the curing, those anhydride linkages will be broken and reacting with epoxy curing agents. In literature, poly(ester-anhydrides) are generally synthesized by acetic anhydride which limits its use in industry. In this study, aliphatic and aromatic cyclic anhydrides were examined for the synthesis of poly(ester-anhydrides) for industrial applications. They were melt mixed with carboxylic acid functional commercial polyesters that have different functionalities in order to investigate the effect of the total functionality on the poly(ester-anhydride) synthesis. Furthermore, a new polyester was synthesized and reacted with an aliphatic cyclic anhydride to gain know-how in polyesters and poly(ester-anhydride) syntheses. According to studies, the synthesis of poly(ester-anhydrides) with succinic anhydride (SA) seems more promising than pyromellitic dianhydride (PMDA) which has limited solubility. It is most likely that, high functionality of PMDA increased both the formation and scission of the targeted anhydride linkages.
Keywords: Polyesters.; Anhydrides.